INFLUENCE OF ORGANIZATIONAL COMMITMENT, WORK SATISFACTION, WORK MOTIVATION TOWARD ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Muchtadin Muchtadin; Chaerudin Chaerudin (Dinasti Publisher, 2020)
The purpose of this study was to measure the effect of organizational commitment, job satisfaction and work motivation on organizational citizenship behavior in SMK Satria Srengseng teachers, this research is quantitative. The population is all teaching teachers and staff. The technique in taking samples uses nonrandom sampling in the form of saturated samples with a total of 70 teachers. Data obtained from the results of the study were analyzed using multiple linear regression. T-test results for the variable organizational commitment, job satisfaction and partial work motivation are positive and significant for organizational citizenship behavior (OCB). F-test results for the variable organizational commitment, job satisfaction and work motivation together are significant for organizational citizenship behavior (OCB). Suggestions for further research are to include other variables that also have a strong influence in shaping organizational citizenship behavior (OCB).